2022
DOI: 10.1128/mbio.03734-21
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Catabolite Repression Governs Diverse Physiological Processes and Development in Aspergillus nidulans

Abstract: The ability to scavenge and use a wide range of nutrients for growth is crucial for microorganisms’ survival in the wild. Carbon catabolite repression (CCR) is a transcriptional regulatory phenomenon of both bacteria and fungi to coordinate the expression of genes required for preferential utilization of carbon sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…SCSIO SX7S7, respectively. The successful mutagenesis of the two genes is easy to monitor, as the inactivity of these two genes usually results in a phenotype change with strong growth defects [ 32 , 33 , 34 , 35 ]. For the Spiromastix sp.…”
Section: Resultsmentioning
confidence: 99%
“…SCSIO SX7S7, respectively. The successful mutagenesis of the two genes is easy to monitor, as the inactivity of these two genes usually results in a phenotype change with strong growth defects [ 32 , 33 , 34 , 35 ]. For the Spiromastix sp.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, CreA suppresses asexual development specifically under glucose but not under maltose, xylose, or ethanol as the sole carbon source. Previous study showed that the unfolded protein response of the Δ creA mutant in A. nidulans is also specific to glucose (Chen et al, 2021). Accordingly, some functions of CreA in addition to CCR depend on carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies of Magnaporthe oryzae (Hong et al, 2021) and Aspergillus flavus (Fasoyin et al, 2018) have suggested that CreA contributes to hyphal growth, asexual development, and pathogenicity. Recently, the functions of CreA have been investigated in A. nidulans by RNA‐seq and ChIP‐seq approaches, revealing direct roles in various pathways, including secondary metabolism, iron homeostasis, oxidative stress, unfolded protein response (UPR), and asexual and sexual developmental processes, in addition to carbon metabolism (Chen et al, 2021). Interestingly, the UPR of a Δ creA mutant was only observed when grown on glucose but not when acetate or proline was used as the sole carbon source (Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In T. reesei , CreA was considered as a regulator of the glucose assimilation rate 51 . Recent research has also shown that CreA could bind not only to the promoter of cellulose related genes, but also to the promoter of other genes to play a primary role in diverse physiological processes, such as carbon metabolism, secondary metabolism, iron homeostasis, oxidative stress response, development, N-glycan production, unfolded protein response, and nutrient and ion transport in A. nidulans 52 . Beyond carbon metabolism regulation, studies in various fungal species indicate additional CreA functions.…”
Section: Discussionmentioning
confidence: 99%